2007
DOI: 10.1177/08857288070300020101
|View full text |Cite
|
Sign up to set email alerts
|

Multicultural Perspectives on Self-Determination From Youth, Parent, and Teacher Focus Groups

Abstract: Numerous curricula and programs have been developed to foster the self-determination of youth with disabilities. Virtually all are rooted in mainstream U.S. values, leading to questions of their relevance and efficacy for culturally and linguistically diverse (CLD) youth who hold different values. To help fill a research gap on cultural influences on self-determination, a focus group methodology was used to explore the perceptions of a diverse range of youth with emotional and/or behavioral disorders, parents,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 28 publications
2
45
0
3
Order By: Relevance
“…Researchers have found, for example, that parents from diverse backgrounds perceive self-determination as an important outcome for their children Leake and Boone 2007); however, parents indicate that how self-determination was operationalized at school was different than how they operationalized it at home. For example, the mothers in study reported an overemphasis on independence, an emphasis that is inconsistent with current definitions of self-determination (Shogren et al 2015a).…”
Section: Limitationsmentioning
confidence: 99%
“…Researchers have found, for example, that parents from diverse backgrounds perceive self-determination as an important outcome for their children Leake and Boone 2007); however, parents indicate that how self-determination was operationalized at school was different than how they operationalized it at home. For example, the mothers in study reported an overemphasis on independence, an emphasis that is inconsistent with current definitions of self-determination (Shogren et al 2015a).…”
Section: Limitationsmentioning
confidence: 99%
“…Those few studies that have begun to explore cultural influences on the manner in which selfdetermination is conceptualized and expressed (e.g., Frankland, Turnbull, Wehmeyer, & Blackmountain;2004;Leake & Boone, 2007) clearly suggest that although there are some universal aspects to our conceptualizations of self-determination, ethnic and cultural belief systems must be understood and taken in to account when attempting to support enhanced outcomes in this area. Further, additional research needs to be undertaken within inclusive settings and on interventions to promote self-determination for all students, including those with IDD who receive their instruction in general education classrooms (Wehmeyer, 2013b).…”
Section: Gaps In the Researchmentioning
confidence: 99%
“…Several researchers have suggested that race/ethnicity may influence selfdetermination. For example, Leake and Boone (2007) used focus groups to get the perspectives of Black, Asian, Filipino, Hawaiian, Hispanic, Pacific Islander, and White students, teachers, and parents about self-determination and identified subtle differences across racial and ethnic groups, particularly related to reported responsibility to families influencing the expression of self-determined behavior. Trainor (2005) reported similar findings for Black, Hispanic, and White youth, but also reported that there was limited congruence between student's self-reported goals and the goals targeted in their school-based transition plan.…”
Section: Microsystemmentioning
confidence: 99%
“…For students with intellectual and developmental disabilities, Carter et al (2011) found that parents tended to report that self-determination skills were important, but that their children engaged in relatively few of the self-determination skills in the home. Leake and Boone (2007) found that parents valued self-determination for their children but sometimes operationalized it differently than their children or the school system. Shogren (2012) found that Hispanic mothers engaged in a number of activities in the home to promote selfdetermination skills, ranging from choice making to goal setting to self-advocacy, but that parents tended to engage in activities very differently than schools.…”
Section: Microsystemmentioning
confidence: 99%